Proportions of nitrate and ammonium and their impact in two species of Poaceae: a study with nanoparticles and ionic nutrients in soil and nutrient solution - Souza Junior, João Cardoso de (2021)
Nitrogen (N) plays a key role in forage grass growth. Studies have shown that the proportions of nitrate and ammonium (NO3-/NH4+) improved the growth of Tanzania guinea grass [Panicum maximum Jacq. cv. Tanzania (syn. Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs)] under copper (Cu) excess. However, no reports are indicating the positive effects of proportions of NO3-/NH4+ for grasses that received Cu via nanoparticles (CuNP), excess manganese (Mn), or submitted to S limitation. For this reason, one experiment with maize (Zea mays L.) and two with Tanzania guinea grass were carried out to confirm the hypothesis that the proportions of NO3-/NH4+ affect the performance of the grasses under conditions of excess nutrient and limitation. The experiments were: i) a factorial 2 × 4 in complete randomized block design with four replications. Factors were: two proportions of NO3-/NH4+ (100/0 and 50/50) combined with four rates of Cu nanoparticles (0, 25, 50, and 100 mg kg-1) in a Spodosol soil from Florida, United States, grown with corn; ii) a factorial 2 × 4 in complete randomized block design with four replications. Factors were: two proportions of NO3-/NH4+ (100/0 and 70/30) combined with four rates of Mn (10, 500, 1,500, and 3,000 µmol L-1) in nutrient solution grown with Tanzania guinea grass and; iii) a factorial 2 × 3 in complete randomized block design with four replications. Factors were: two proportions of NO3-/NH4+ (100/0 and 70/30) combined with three rates of sulfur (S) (0.1, 1.0, and 2.0 mmol L-1) in nutrient solution grown with Tanzania guinea grass. Experiment i) the dry biomass of maize plants was high at 100/0 NO3-/NH4+, which provided greater concentration and accumulation of Cu in the shoots and roots, as well as better growth, photosynthesis, nutrient accumulation, and high rhizosphere soil pH, improving the availability of important nutrients, as well as mitigating toxic effects of CuNP. Experiment ii) The excess Mn at 3,000 µmol L-1 did not affect the dry biomass of Tanzania guinea grass. The maximum concentration of Mn was obtained in the plants that received a combination of all N as N NO3- and Mn at 3,000 µmol L-1, with higher averages than that reported for hyperaccumulators plants. This effect induced oxidative stress in the grass, negatively affecting the activity of glutamine synthetase and photosynthesis. However, for that condition, there was an increase in the proline concentration, which was related to better plant survival in a situation of excess Mn. Experiment iii) in a situation with sufficient S, plants receiving 70/30 NO3-/NH4+ grown better and accumulated more S than those plants are grown with NO3- solely. The application of NH4+ for plants under S limitation showed a high accumulation of NO3- in the roots. However, the S limitation decreased the photosynthetic activity in the plants grown with NO3- solely, but not in the plants that received both NO3- and NH4+. The S limitation caused oxidative stress, which was mitigated by guaiacol peroxidase and stimulated by the positive effects of NO3- and NH4+. Proportions of NO3-/NH4+change the performance of two species of Poaceae in conditions of excess and nutrient limitation, even in the form of nanoparticles, indicating that N fertilization must be carefully applied, considering proportions between N ions and abiotic conditions imposed to plants.